วิวัฒนาการของแนวคิดเกี่ยวกับสิทธิทางการศึกษาในประเทศไทย - กัญญา สุขสบาย (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
Examine the evolution of the perspectives on educational rights in Thai education system from the range of B.E. 2435-2540. Research methods are documentary research and analytic induction. 11 perspectives are thoroughly examined : (1) the right to free and compulsory education, (2) the right to secondary education in different forms by all appropriate means, (3) the right to equal access to higher education, (4) the right to acquire fundamental literacy, (5) the right to lifelong education, (6) the right to learn the values and customs of one s group, (7) the right to obtain vocational guidance, (8) the right to learn about human right, (9) the right of parents to choose the kind of education that will be given to their children, (10) the right to freedom of thought, conscience and religion, (11) the right to educational participation. The study revealed that from the first period of B.E. 2435-2464, 7 perspectives on the educational rights are stated. There are 6 issues (1, 3, 4, 9, 10, 11) found in legalized documents and 4 perspectives on educational rights (1, 6, 10, 11). The second period of B.E. 2464-2474, 4 perspectives on the educational rights are stated. There are 3 issues (1, 9, 11) found in legalized documents and 1 perspectives on educational rights (10). The third period of B.E. 2475-2487, 7 perspectives on the educational rights are stated. There are 4 issues (1, 3, 10, 11) found in legalized documents and 7 perspectives on educational rights (1, 3, 4, 8, 9, 10, 11). The fourth period of B.E. 2488-2503, 8 perspectives on the educational rights are stated. There are 5 issues (1, 3, 6, 10, 11) found in legalized documents and 5 perspectives on educational rights (1, 2, 3, 4, 9). The fifth period of B.E. 2504-2515, 7 perspectives on the educational rights are stated. There are 3 issues (1, 3, 11) found in legalized documents and 7 perspectives on educational rights (1, 2, 3, 4, 7, 9, 11). The sixth period of B.E. 2516-2540, 11 perspectives on the educational rights are stated. There are 6 issues (1, 3, 5, 6, 10, 11) found in legalized documents and 7 perspectives on educational rights are found in all 11 issues.